Efficacy and safety of baricitinib in Japanese patients with rheumatoid arthritis: Subgroup analyses of four multinational phase 3 randomized trials. Issue 4 (4th July 2018) - Tanaka, Yoshiya; Atsumi, Tatsuya; Amano, Koichi; Harigai, Masayoshi; Ishii, Taeko; Kawaguchi, Osamu; Rooney, Terence P.; Akashi, Naotsugu; Takeuchi, Tsutomu
Abstract: Objectives: To evaluate efficacy/safety of baricitinib for rheumatoid arthritis (RA) in Japanese subpopulations from four phase 3 studies, and assess whether results in these subpopulations are consistent with the overall study populations. Methods: Subgroup analyses (394 patients) of four phase 3 randomized controlled trials: RA-BEGIN [no or limited treatment with disease-modifying antirheumatic drugs (DMARDs)], RA-BEAM [inadequate response (IR) to methotrexate], RA-BUILD [IR to conventional synthetic DMARDs (csDMARDs)], and RA-BEACON (IR to tumor necrosis factor inhibitors receiving csDMARDs). Results: For American College of Rheumatology 20% improvement (ACR20) response rate, Japanese patients receiving baricitinib 4-mg showed similar improvement compared to methotrexate at Week 24 (72 versus 69%; RA-BEGIN), and greater improvement compared with placebo at Week 12 (67 versus 34%; RA-BEAM). Japanese patients receiving baricitinib 4-mg also showed greater improvement compared with placebo at Week 12 in RA-BUILD and RA-BEACON. Across all studies, baricitinib was well-tolerated, with no deaths and one malignancy. In RA-BEGIN and RA-BEAM, herpes zoster rates were higher for Japanese patients than for overall populations; all events were mild/moderate. Conclusion: Data for baricitinib, with/without methotrexate, in Japanese subpopulations across all stages of the RA treatment continuum accord with the efficacy/safety profile in overall study populations. Baricitinib appears to be similarly effective in Japanese patients.